Imunossupressão causada por domínios repetitivos presentes em antígenos do Trypanosoma cruzi - Carlos Andrés Toro Acevedo (2017)
Amino acid repeats are present in all organisms. However, the predicted proteomes of intracellular parasites have a higher content of repetitive domains than the proteomes of extracellular parasites or free living microorganisms. The presence of repeat domains has been associated with the immune-evasion capacity of different pathogens. The ribosomal Trypanosoma cruzi L7a protein contains a repeat domain at its N-terminus. To investigate the role of this repeat domain, we produced three versions of the recombinant, corresponding to the entire protein (TcL7a) and the truncated version that contains only the repeats (TcL7aRep) or the non-repetitive region (TcL7aΔRep). Immunization of BALB/c mice with these three proteins, followed by challenge with bloodstream trypomastigotes of the CL Brener clone showed that immunization with the complete TcL7a protein protected the animals against T. cruzi infection since parasitemia and mortality were diminished, while the immunization with the non-repetitive TcL7aΔRep did not result in a significant effect. Surprisingly, immunization with the repeat domain TcL7aRep results in exacerbated parasitemia and mortality in all infected animals. To elucidate the mechanism by which the TcL7aRep augments the susceptibility of mice to infection, we evaluated the specific antibody production against T. cruzi whole cell extracts in sera from infected animals. We observed lower levels of IgM and total IgG antibodies against the protein extract of T. cruzi in immunized and infected animals compared with infected animals that were not immunized (control). After splenocyte in vitro stimulation with concanavalin A and α-CD3, we observed that, when splenocytes are incubated with TcL7aRep, CD4+ and CD8+ T lymphocytes and CD19+ B lymphocytes were less able to proliferate than control lymphocytes. Additionally, a 24 hours incubation with TcL7aRep before stimulation resulted in a decrease of surface important molecules for adaptive response, such as CD3, CD4, CD8 and CD25 in lymphocytes from spleen obtained from non-infected mice. Taken together, our data indicates that animals immunized with TcL7aRep or splenocytes incubated in vitro with this antigen present an immunossupressive phenotype, which could explain the higher susceptibility to infection with T. cruzi of all animals immunized with the repeat domain. Similar to other studies that investigated the role other T. cruzi antigens, such as trans-sialidase containing the SAPA repeats, our study correlates the existence of an immunossupressive mechanism caused by parasite antigenic repeats as part of its strategy to survive inside the mammal host.